Sistem Monitoring Tambak Ikan berbasis Internet of Things menggunakan ESP32 - Al attas, Said Usman Sulaiman; Wicaksono, Muhammad Jaka Wimbang; Futra, Asrizal Deri; Diono, Diono; Aryeni, Illa; Sani, Abdullah (Journal of Applied Electrical Engineering, 2024)
Upredictable natural conditions cause fish larvae to die because they cannot adapt to these conditions, leading to potential harvest failure. Changes in natural conditions due to weather result in unstable pH levels in pond water. Fish Farmers traditionally attempt to improve water pH quality using by manual pH meters, but This method has limitations if not monitored periodically. Based on this problems, researchers plan to develop a water acidity measurement tool using an IoT-based E4502C pH sensor to help fish farmers monitor pond pH levels through their smartphones. Testing the pH sensor showed an average error rate of 4.09% at pH 4, 2.47% at pH 7, and 6.31% at pH 9. More accurate results can be achieved by collecting more data and processing it to determine the average values before displaying them on the user interface.